2019
DOI: 10.1200/jco.2019.37.15_suppl.4040
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination deficiency as prognostic marker in metastatic gastric cancer.

Abstract: 4040 Background: Gastric cancer is the 5th cancer diagnosis and 3rd cause of cancer death worldwide. Metastatic gastric cancer (mGC) has a median survival of 11 months. mGC is an heterogeneous disease and different biologic characteristics may justify differential therapeutic opportunities. Tumors with homologous recombination (HR) deficiency may benefit with treatment with PARP inhibitors or immune checkpoint inhibitors. The purpose of this study was to evaluate the prevalence and prognostic impact of altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Here we describe the HRD signature landscape derived from whole-genome sequencing (WGS) of gastrointestinal (GI) and thoracic malignancies sequenced as part of the Personalized OncoGenomics program in British Columbia, Canada and characterize the relationship between HRD and clinical outcomes with platinum-based treatment. Retrospective studies to date have suggested an association between platinum response and selected HRD mutations in pancreatic, colorectal, gastric, and lung cancers, although these studies have largely focused on pre-selected HRD mutations rather than a WGS approach 6 , 8 , 32 , 33 . Gastrointestinal and thoracic malignancies were selected for this analysis due to the relative paucity of data in these tumor sites, particularly when compared to breast and ovarian cancers, as well as their routine use of platinum therapies with the potential for HRD to underlie heterogeneity in clinical response 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Here we describe the HRD signature landscape derived from whole-genome sequencing (WGS) of gastrointestinal (GI) and thoracic malignancies sequenced as part of the Personalized OncoGenomics program in British Columbia, Canada and characterize the relationship between HRD and clinical outcomes with platinum-based treatment. Retrospective studies to date have suggested an association between platinum response and selected HRD mutations in pancreatic, colorectal, gastric, and lung cancers, although these studies have largely focused on pre-selected HRD mutations rather than a WGS approach 6 , 8 , 32 , 33 . Gastrointestinal and thoracic malignancies were selected for this analysis due to the relative paucity of data in these tumor sites, particularly when compared to breast and ovarian cancers, as well as their routine use of platinum therapies with the potential for HRD to underlie heterogeneity in clinical response 34 .…”
Section: Introductionmentioning
confidence: 99%